An Insight Into the Potentiation Effect of Potassium Iodide on aPDT Efficacy - Vieira, Cátia; Gomes, Ana T. P. C.; Mesquita, Mariana Q.; Moura, Nuno M. M.; Neves, M. Graça P. M. S.; Faustino, M. Amparo F.; Almeida, Adelaide (Frontiers in Microbiology, 2018)
Antimicrobial photodynamic therapy (aPDT) is gaining a special importance as an effective approach against multidrug-resistant strains responsible of fatal infections. The addition of potassium iodide (KI), a non-toxic salt, is recognized to increase the aPDT efficiency of some photosensitizers (PSs) on a broad-spectrum of microorganisms. As the reported cases only refer positive aPDT potentiation results, in this work we selected a broad range of porphyrinic and non-porphyrinic PSs in order to gain a more comprehensive knowledge about this aPDT potentiation by KI. For this evaluation were selected a series of meso-tetraarylporphyrins positively charged at meso positions or at β-pyrrolic positions and the non-porphyrinic dyes Methylene blue, Rose Bengal, Toluidine Blue O, Malachite Green and Crystal Violet; the assays were performed using a bioluminescent E. coli strain as a model. The results indicate that KI has also the ability to potentiate the aPDT process mediated by some of the cationic PSs (Tri-Py(+)-Me, Tetra-Py(+)-Me, Form, RB, MB, Mono-Py(+)-Me, β-ImiPhTPP, β-ImiPyTPP and β-BrImiPyTPP) allowing a drastic reduction of the treatment time as well as of the PS concentration. However, the efficacy of some porphyrinic and non-porphyrinic PSs (Di-Py(+)-Me opp, Di-Py(+)-Me adj, Tetra-Py, TBO, CV and MG) was not improved by the presence of the coadjuvant. For the PSs tested in this study, the ones capable to decompose the peroxyiodide into iodine (easily detectable by spectroscopy or by the visual appearance of a blue colour in the presence of amylose) were the most promising ones to be used in combination with KI. Although these studies confirmed that the generation of 1O2 is an important fact in this process, the PS structure (charge number and charge position), aggregation behavior and affinity for the cell membrane are also important features to be taken in account.